GAYO’S LINGUA TOURISM: AN EMPIRICAL STUDY ON ENGLISH NEEDS AND STRATEGIES - Desi Purnama Sari; Sulistio Ningsih; Ranti Maulya; Kamarullah Kamarullah; Rahmaini Fitri (Universitas Bina Bangsa Getsempena, 2025)
This study explores the English language proficiency of tourism players in the Gayo Highlands and suggests strategic training paths under the English for Tourism (EfT) model. The design that was used was a quantitative, cross-sectional design using a Likert-scale questionnaire to measure the four core skills, which are listening, speaking, reading, and writing. The results indicated that there was a high difference between the receptive and productive skills, with listening and reading being much better compared to speaking and writing. The Pearson correlation analysis also revealed that listening and speaking skills (r = 0.95) were highly correlated, and it is worth discussing the pedagogical significance of the integrated input-output strategies. The findings highlight the importance of communication and culturally responsive training programs, which address the authentic language utilization that is necessitated in the ecotourism and heritage settings of Gayo. This is in accordance with previous studies that underscored the expectations of the society of the tourism actors not only to apply English functionally but also to project cultural identity by means of language. Practical suggestions are the use of mobile-assisted learning devices, participatory training creation, and stakeholder collaboration among local agencies and training institutions. The research has both theoretical contributions to the ESP/EfT scholars and practical usefulness to the policymakers and tourism developers who are concerned with sustainable language learning.